2008
DOI: 10.1088/0022-3727/41/10/105013
|View full text |Cite
|
Sign up to set email alerts
|

Strain-driven inverse thermal hysteresis behaviour in half-doped manganites

Abstract: In this paper, we report unusual thermal hysteresis behaviour in half-doped manganites Nd0.5Sr0.5−xCaxMnO3 (0.0 ⩽ x ⩽ 0.50). For 0.05 ⩽ x < 0.25 samples, the magnetization curves show a counterclockwise hysteresis loop. For 0.25 < x ⩽ 0.40 samples, however, they exhibit a clockwise loop. The inverse hysteretic behaviour stems from the competition between two kinds of strain, namely, the compressive strain and the tensile strain. The former produces a counterclockwise thermal hysteresis while the latter leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The FM transition with lower T C shows normal thermal hysteresis and the other FM transition shows inverse thermal hysteresis. The inverse thermal hysteresis has been observed only in a few compounds , and thus, it represents a rare phenomenon. The reason for this rare phenomenon is discussed in Section .…”
Section: Resultsmentioning
confidence: 99%
“…The FM transition with lower T C shows normal thermal hysteresis and the other FM transition shows inverse thermal hysteresis. The inverse thermal hysteresis has been observed only in a few compounds , and thus, it represents a rare phenomenon. The reason for this rare phenomenon is discussed in Section .…”
Section: Resultsmentioning
confidence: 99%
“…Polycrystalline samples Nd 0.5 Ca 0.5−x Sr x MnO 3 (0.10 ≤ x ≤ 0.25) were prepared by the conventional solid-state reaction method and were referred to be CS41 (x = 0.1), CS32 (x = 0.2), and CS25 (x = 0.25) [22]. Their structures and phase purities were checked by X-ray powder diffraction.…”
Section: Methodsmentioning
confidence: 99%
“…Both of them all exhibit insulator CO-AFM ground state. However, when we change the ratio of Ca 2+ /Sr 2+ ions [22], the CO-AFM phase can be broken and the electronic transport behavior reveals an IMT. Obviously, such an IMT is directly related to the presence of intrinsic disorder which spontaneously forms in the system due to the size mismatch on the A-site sublattice.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies, it was shown that the short-range and inhomogeneous strain plays an important role in the first-order magnetic phase transition of LPCMO. [16][17][18][19] Accompanied by the COI-to-FMM phase transition, the interfacial elastic energy arises due to the coexistence of FMM and COI domains with distinct lattice mismatch and different surface/volume ratios. 19 The increase of the interfacial elastic energy in turn raises the energy barrier and impedes the growth of FMM phase.…”
mentioning
confidence: 99%
“…[16][17][18][19] Accompanied by the COI-to-FMM phase transition, the interfacial elastic energy arises due to the coexistence of FMM and COI domains with distinct lattice mismatch and different surface/volume ratios. 19 The increase of the interfacial elastic energy in turn raises the energy barrier and impedes the growth of FMM phase. [16][17][18] With the thermal cycling within the FMM-COI coexistence temperature region ͑between 10 K and ϳT CO , in the present case͒, the intertransition between FMM and COI phases may bring out additional FMM-COI interfacial regions that increase the interfacial elastic energy and complicate the freeenergy landscape.…”
mentioning
confidence: 99%